Simulasi Setting WLC berdasarkan kebijakan VLAN pada Client yang terhubung ke AP di Gedung Gamma (Administrasi) Sekolah Vokasi IPB - Aep Setiawan (LPPM Universitas Putera Batam, 2023)
IPB University Vocational School has several buildings including the Gamma Building as an administrative center. In the Gamma Building several access points were installed to support administrative activities. The gamma building consists of 4 floors where each floor has different needs. The 1st floor is for student administration activities, the 2nd floor is for financial administration, data and leadership rooms, the 3rd floor is lecturer meeting rooms and leadership rooms and the 4th floor is lecturer meeting rooms and lecturer rooms. Management is required to set the AP point configuration based on the SSID, so WLC is used to set the SSID based on the VLAN created. The methods used in making this simulation are observation, design and testing. Observations were carried out to see the need for access points in the gamma building and what SSIDs would be created, including VLAN 10 SSID for leadership, VLAN 20 SSID for lecturers, VLAN 30 SSID for students, VLAN 40 SSID for staff and VLAN 50 SSID for guests. Design is the process of making a network topology in a Cisco packet tracer simulation based on observations. Tests are carried out whether the SSID is obtained by each client based on a certain VLAN. Obtained from the results of SSID testing on each floor based on the provisions where on the 1st floor all SSID, on the 2nd floor Leaders, Lecturers and staff, on the 3rd floor Leaders, lecturers and guests and on the 4th floor leaders and lecturers. Each client gets its SSID based on the VLAN that is set.